Immune cell labelling and tracking: implications for adoptive cell transfer therapies - Filippo Galli; Michela Varani; Chiara Lauri; Guido Gentiloni Silveri; Livia Onofrio; Alberto Signore (SpringerOpen, 2021)
Abstract Background The understanding of the role of different immune cell subsets that infiltrate tumors can help researchers in developing new targeted immunotherapies to reactivate or reprogram them against cancer. In addition to conventional drugs, new cell-based therapies, like adoptive cell transfer, proved to be successful in humans. Indeed, after the approval of anti-CD19 CAR-T cell therapy, researchers are trying to extend this approach to other cancer or cell types. Main body This review focuses on the different approaches to non-invasively monitor the biodistribution, trafficking and fate of immune therapeutic cells, evaluating their efficacy at preclinical and clinical stages. PubMed and Scopus databases were searched for published articles on the imaging of cell tracking in humans and preclinical models. Conclusion Labelling specific immune cell subtypes with specific radiopharmaceuticals, contrast agents or optical probes can elucidate new biological mechanisms or predict therapeutic outcome of adoptive cell transfer therapies. To date, no technique is considered the gold standard to image immune cells in adoptive cell transfer therapies.